2006
DOI: 10.1097/00130404-200605000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Placebo-Controlled, Randomized Trial of Granulocyte-Colony Stimulating Factor During Postoperative Radiotherapy for Squamous Head and Neck Cancer

Abstract: Granulocyte-colony stimulating factor during radiotherapy was feasible and led to significantly shorter radiotherapy duration and trends toward less percutaneous endoscopic gastrostomy placement and mucositis. The unanticipated improvement in survival outcomes warrants further hypothesis-driven investigation and validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 12 publications
0
17
0
3
Order By: Relevance
“…The same therapeutic strategy was applied in a patient with advanced hepatocarcinoma, who exhibited a complete remission after 4 months of G-CSF treatment. Prolonged administration of G-CSF to squamous head and neck cancer patients led to increased disease-free survival [320]. Other clinical trials using continuous GM-CSF administration in advanced prostate cancer [321] or sustained G-CSF in stage IV melanoma with brain metastases [322] reported better survival, suggesting for an anti-tumor effects of neutrophils.…”
Section: Major Findings Referencementioning
confidence: 99%
“…The same therapeutic strategy was applied in a patient with advanced hepatocarcinoma, who exhibited a complete remission after 4 months of G-CSF treatment. Prolonged administration of G-CSF to squamous head and neck cancer patients led to increased disease-free survival [320]. Other clinical trials using continuous GM-CSF administration in advanced prostate cancer [321] or sustained G-CSF in stage IV melanoma with brain metastases [322] reported better survival, suggesting for an anti-tumor effects of neutrophils.…”
Section: Major Findings Referencementioning
confidence: 99%
“…Two cohort studies did not find a benefit for the use of this growth factor [44,45] in these patients, whereas a small study by Schneider et al [46] reported only preliminary results. Since then, only one study on the use of systemic G-CSF for the prevention of oral mucositis induced by (C)RT for H&N cancers has been published [47]. This study reported a non-significant trend for a beneficial effect of this intervention but was closed prematurely because of low accrual.…”
Section: Granulocyte Colony-stimulating Factormentioning
confidence: 99%
“…Further, Rini et al, who administered GM‐CSF alone (another cytokine closely related to G‐CSF), reported that 25% of patients with relapsed prostate cancer remained free of disease progression at a median of 5 years after the start of therapy 427. However, the strongest argument in favor of the therapeutic anticancer effect of the prolonged administration of G‐CSF, i.e., causing sustained neutrophilia, comes from a randomized, double‐blind, placebo‐controlled trial designed to evaluate the ability of G‐CSF to reduce mucositis during postoperative radiotherapy for locoregionally advanced stages of head and neck cancer (follow‐up was for 10 years) 428. Despite the fact that the study was prematurely ended because of slow accrual, 40 patients were evaluated.…”
Section: Pmn and The Dynamics Of Tumor Growthmentioning
confidence: 99%